Biomarkers for arterial and venous thrombotic disorders - Mannhalter, C. (Hämostaseologie, 2014)
The haemostatic system maintains the blood in a fluid state, but allows rapid clot formation at sites of vascular injury to prevent excessive bleeding. Unbalances within the haemostatic system can lead to thrombosis. Inspite of successful research our understanding of the disease pathogenesis is still incomplete. There is great hope that genetic, genomic, and epigenetic discoveries will enhance the diagnostic capability, and improve the treatment options. During the preceding 20 years, the identification of polymorphisms and the elucidation of their role in arterial and venous thromboses became an important area of research. Today, a large body of data is available regarding associations of single nucleotide polymorphisms (SNPs) in candidate genes with plasma concentrations and e. g. the risk of ischaemic stroke or myocardial infarction. However, the results for individual polymorphisms and genes are often controversial. It is now well established that besides acquired also hereditary risk factors influence the occurrence of thrombotic events, and environmental factors may add to this risk. Currently available statistical methods are only able to identify combined risk genotypes if very large patient collectives (>10 000 cases) are tested, and appropriate algorithms to evaluate the data have yet to be developed. Further research is needed to understand the functional effects of genetic variants in genes of blood coagulation proteins that are critical to the pathogenesis of arterial and venous thrombotic disorders. In this review genetic variants in selected genes of the haemo static system and their relevance for arterial and venous thrombosis will be discussed.
Keywords: Genetics; single nucleotide polymorphisms; thrombotic disorders; haemostasis